Ответ:
[tex]a)\ -2\\b)\ -5\\g)\ 13\\m)\ 21[/tex]
Объяснение:
[tex]a)\\\\(2+\sqrt 6)(2-\sqrt 6)=2^2-(\sqrt6)^2=4-6=-2\\\\b)\\\\(\sqrt7+\sqrt 2)(\sqrt2-\sqrt7)=(\sqrt2+\sqrt 7)(\sqrt2-\sqrt7)=\\\\(\sqrt2)^2-(\sqrt7)^2=2-7=-5\\\\g)\\\\(2\sqrt5-\sqrt7)(\sqrt7+2\sqrt5)=(2\sqrt5-\sqrt7)(2\sqrt5+2\sqrt7)=\\\\(2\sqrt5)^2-(\sqrt7)^2=20-7=13\\\\m)\\\\(\sqrt3 +2\sqrt6)(\sqrt{24}-\sqrt3)=(2\sqrt6+\sqrt3)(2\sqrt{6}-\sqrt3)=\\\\(2\sqrt6)^2-(\sqrt3)^2=24-3=21[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]a)\ -2\\b)\ -5\\g)\ 13\\m)\ 21[/tex]
Объяснение:
[tex]a)\\\\(2+\sqrt 6)(2-\sqrt 6)=2^2-(\sqrt6)^2=4-6=-2\\\\b)\\\\(\sqrt7+\sqrt 2)(\sqrt2-\sqrt7)=(\sqrt2+\sqrt 7)(\sqrt2-\sqrt7)=\\\\(\sqrt2)^2-(\sqrt7)^2=2-7=-5\\\\g)\\\\(2\sqrt5-\sqrt7)(\sqrt7+2\sqrt5)=(2\sqrt5-\sqrt7)(2\sqrt5+2\sqrt7)=\\\\(2\sqrt5)^2-(\sqrt7)^2=20-7=13\\\\m)\\\\(\sqrt3 +2\sqrt6)(\sqrt{24}-\sqrt3)=(2\sqrt6+\sqrt3)(2\sqrt{6}-\sqrt3)=\\\\(2\sqrt6)^2-(\sqrt3)^2=24-3=21[/tex]